Organizational Forms and Incentives in Public Procurement: Natural Experiment at a Large Public Sector Organization in Russia. Issue 14 (26th October 2018) - Tkachenko, Andrey; Yakovlev, Andrei; Rodionova, Yuliya
ABSTRACT: This article analyses how the intensification of centralized monitoring within public organization may impact incentives for efficiency in those divisions of the organization that have different levels of financial autonomy. The efficiency of divisions' activities was estimated through their procurement effectiveness. All the divisions were classified as non-commercial units (NCU) funded by the government or as income earning units (IEU) operating in the market and having broader financial autonomy. The results show that under standard monitoring, the IEU had more efficient procurements compared to the NCU. After intensification of centralized monitoring, the differences in performance became insignificant. These findings show that stricter monitoring is efficient for organizations with soft budget constraints, while for organizations with hard budget constraints it is preferable to use more flexible regulations.